Development of Perceived Familial and Non-familial Support in Adolescence; Findings From a Community-Based Longitudinal Study - Spitz, Andrea; Winkler Metzke, Christa; Steinhausen, Hans-Christoph (Frontiers in Psychology, 2020)
There are pronounced developmental changes in perceived social support during adolescence. The present study used the newly developed Adolescent Social Support Questionnaire (ASSQ) to examine both the consultation frequency of, and the satisfaction with perceived social support across adolescence in a longitudinal study focussing on nine different familial and non-familial supporters. The sample of N=857 adolescents was derived from the Zurich Adolescent Psychology and Psychopathology Study (ZAPPS) and included three measurement time points. Overall, there was a decrease in the perceived frequency and satisfaction from adolescents with social support from both parents and grandparents from preadolescence to late adolescence. Best friends and romantic partners were consulted more frequently, and their support was perceived as more satisfying with increasing age. Teachers were contacted more frequently with increasing age, while satisfaction with their support remained stable. In contrast, though contacted less frequently, brothers and other relatives showed no changes in perceived satisfaction with support during adolescence. Parents and best friends were perceived as the most satisfying supporters during adolescence followed by romantic partners in later adolescence. Grandparents were perceived as an important support source but only in preadolescence. There were developmental differences during the various stages of adolescence with regard to the importance placed on each social support source. Both parents remained a very a satisfying support source, although they were consulted less often. Romantic partners and best friends gained importance as supporters in older adolescents, whereas grandparents represented a more important support source for preadolescents. Although teachers were not frequently consulted, they remained a stable and satisfying source of support.